2016
DOI: 10.18632/oncotarget.8775
|View full text |Cite
|
Sign up to set email alerts
|

The landscape of targeted therapies for cholangiocarcinoma: current status and emerging targets

Abstract: Cholangiocarcinoma (CCA) is a relatively rare malignancy that arises from the epithelial cells of the intrahepatic, perihilar and distal biliary tree. Intrahepatic CCA (ICC) represents the second most common primary liver cancer, after hepatocellular cancer. Two-thirds of the patients with ICC present with locally advanced or metastatic disease. Despite standard treatment with gemcitabine and cisplatin, prognosis remains dismal with a median survival of less than one year. Several biological plausibilities can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
89
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(90 citation statements)
references
References 100 publications
1
89
0
Order By: Relevance
“…Since the prognosis of CCA remains poor with traditional chemotherapy, in the era of personalized medicine several research teams have been working on the molecular and genetic characterization of CCA to identify molecular targets (5)(6)(7)(8)14). Landscape of signalling pathways offers multiple therapeutic targets including growth factor receptors (GFRs) like epidermal (EGFR), vascular (VEGFR), human epidermal growth factor receptor 2 (HER2), the ligand of VEGFR (VEGF) and their downstreaming signal molecules of RAS-RAF-MEK-ERK and PI3K-ACT-mTOR (5)(6)(7)(8)14). Targetspecific monoclonal antibodies and tyrosine kinase inhibitors are able to block selectively the over-expressed or over-activated signal molecules potentiating the growth and invasion of CCA cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the prognosis of CCA remains poor with traditional chemotherapy, in the era of personalized medicine several research teams have been working on the molecular and genetic characterization of CCA to identify molecular targets (5)(6)(7)(8)14). Landscape of signalling pathways offers multiple therapeutic targets including growth factor receptors (GFRs) like epidermal (EGFR), vascular (VEGFR), human epidermal growth factor receptor 2 (HER2), the ligand of VEGFR (VEGF) and their downstreaming signal molecules of RAS-RAF-MEK-ERK and PI3K-ACT-mTOR (5)(6)(7)(8)14). Targetspecific monoclonal antibodies and tyrosine kinase inhibitors are able to block selectively the over-expressed or over-activated signal molecules potentiating the growth and invasion of CCA cells.…”
Section: Discussionmentioning
confidence: 99%
“…In CCA the frequency of BRAF V600E has been reported to range 0-12% in EH and 0-22% in IH subtypes (5)(6)(7)(8)14). Although BRAF V600 can serve as a potential molecular target in CCA, until now there was no evidence of benefit using BRAF inhibitor therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic studies of biliary tumors have identified known growth factor gene mutations [100,101] and signaling pathways [102] that control tumor growth and survival. Target-specific monoclonal antibodies and small molecule inhibitors directed against the signaling pathways that promote the growth and spread of cholangiocarcinoma are being developed [103].…”
Section: Molecular Targeted Agentsmentioning
confidence: 99%
“…Other novel mutations include isocitrate dehydrogenase (IDH), BRCA1-associated protein 1 (BAP1) and AT-rich interactive domain-containing protein 1A (ARID1A), and novel fusions such as fibroblast growth factor receptor 2 (FGFR2) and ROS proto-oncogene 1 (ROS1) [100].…”
Section: Molecular Targeted Agentsmentioning
confidence: 99%